2015
DOI: 10.1152/physiolgenomics.00107.2014
|View full text |Cite
|
Sign up to set email alerts
|

Conditional disruption of miR17-92 cluster in collagen type I-producing osteoblasts results in reduced periosteal bone formation and bone anabolic response to exercise

Abstract: In this study, we evaluated the role of the microRNA (miR)17-92 cluster in osteoblast lineage cells using a Cre-loxP approach in which Cre expression is driven by the entire regulatory region of the type I collagen α2 gene. Conditional knockout (cKO) mice showed a 13-34% reduction in total body bone mineral content and area with little or no change in bone mineral density (BMD) by DXA at 2, 4, and 8 wk in both sexes. Micro-CT analyses of the femur revealed an 8% reduction in length and 25-27% reduction in tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 37 publications
1
34
0
Order By: Relevance
“…) (Wei et al, ), indicating that miR‐21 is a mechanosensitive associated miRNA in the regulation of bone formation under mechanical loading. Moreover, expression of MiR‐20a and miR‐92a increased 1.3‐ and 2.1‐folds respectively in the mechanically loaded tibia compared to the unloaded tibia following 2 weeks of four‐point bending in C57BL/6J mice (Mohan et al, ).…”
Section: Mechanical Stress‐mediated Bone Metabolism Through Micrornasmentioning
confidence: 99%
See 2 more Smart Citations
“…) (Wei et al, ), indicating that miR‐21 is a mechanosensitive associated miRNA in the regulation of bone formation under mechanical loading. Moreover, expression of MiR‐20a and miR‐92a increased 1.3‐ and 2.1‐folds respectively in the mechanically loaded tibia compared to the unloaded tibia following 2 weeks of four‐point bending in C57BL/6J mice (Mohan et al, ).…”
Section: Mechanical Stress‐mediated Bone Metabolism Through Micrornasmentioning
confidence: 99%
“…The response of bone tissue cells to a mechanical stress stimulus is adversely affected when critical miRNAs are missing. Mohan et al () reported that conditional disruption of the miR17‐92 cluster in collagen type I‐producing osteoblasts reduced the bone mineral density and bone strength, decreased bone formation rate significantly, and down‐regulated the gene expression of periostin, Elk3, and Runx2. Furthermore, the periosteal bone response to mechanical strain was obviously decreased due to conditional knockout of miR17‐92 cluster (Mohan et al, ).…”
Section: Mechanical Stress‐mediated Bone Metabolism Through Micrornasmentioning
confidence: 99%
See 1 more Smart Citation
“…54 Another study indicated that in osteoblasts conditional disruption of miR17-92 cluster, which is activated by IGF-1 stimulation, results in reduced periosteal bone formation and bone anabolic response to exercise. 55 In vitro data support these vivo observations. Inhibition of IGF-1with the antagonist IGFBP-4 blunted fluid-flow stress-induced proliferation in the osteoblastic cell line MC3T3-E1.…”
Section: Role Of Igf-1 In the Osteoblast Response To Mechanical Stimulimentioning
confidence: 71%
“…We further assessed the skeletal response of osteoblast‐specific IGF‐1R deficient mice to unloading and reloading, and found that the recovery of periosteal bone formation with reloading was completely inhibited in the conditional IGF‐1R knockout mice . Another study indicated that in osteoblasts conditional disruption of miR17‐92 cluster, which is activated by IGF‐1 stimulation, results in reduced periosteal bone formation and bone anabolic response to exercise …”
Section: Role Of Igf‐1 In the Mesenchymal Stem Cell Response To Mechamentioning
confidence: 99%